2005
DOI: 10.1073/pnas.0409896102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of familial hemiplegic migraine type 1 mutations on neuronal P/Q-type Ca 2+ channel activity and inhibitory synaptic transmission

Abstract: Inhibitory synapses play key roles in the modulatory circuitry that regulates pain signaling and generation of migraine headache. A rare, dominant form of this common disease, familial hemiplegic migraine type 1 (FHM1), arises from missense mutations in the pore-forming ␣1A subunit of P͞Q-type Ca 2؉ channels. These channels are normally vital for presynaptic Ca 2؉ entry and neurotransmitter release at many central synapses, raising questions about effects of FHM1 mutations on neuronal Ca 2؉ influx and inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 50 publications
1
50
0
Order By: Relevance
“…In humans, mutations in the CACNA1A gene cause, in addition to FHM1, a few autosomal dominant neurological disorders characterized by cerebellar dysfunction, such as episodic ataxia type 2 (that may be associated with absence epilepsy in a few cases) and spinocerebellar ataxia type 6 9,26,27 (compare, Strupp 28 and Gomez 29 31,35,37,38 Recently, the generation of knockin mice carrying two different FHM1 mutations (R192Q and S218L) allowed the first analysis of mutant channels expressed at their endogenous level in neurons. [39][40][41] The studies in heterologous expression systems showed that the FHM1 mutations alter many biophysical properties of human Ca V 2.1 channels, in a complex way.…”
Section: Familial Hemiplegic Migraine Type 1 (Fhm1)mentioning
confidence: 99%
See 2 more Smart Citations
“…In humans, mutations in the CACNA1A gene cause, in addition to FHM1, a few autosomal dominant neurological disorders characterized by cerebellar dysfunction, such as episodic ataxia type 2 (that may be associated with absence epilepsy in a few cases) and spinocerebellar ataxia type 6 9,26,27 (compare, Strupp 28 and Gomez 29 31,35,37,38 Recently, the generation of knockin mice carrying two different FHM1 mutations (R192Q and S218L) allowed the first analysis of mutant channels expressed at their endogenous level in neurons. [39][40][41] The studies in heterologous expression systems showed that the FHM1 mutations alter many biophysical properties of human Ca V 2.1 channels, in a complex way.…”
Section: Familial Hemiplegic Migraine Type 1 (Fhm1)mentioning
confidence: 99%
“…While either an increase or a decrease of the whole cell Ca V 2.1 current density elicited by strong depolarizations was measured in HEK293 cells depending on the FHM1 mutant analyzed 31,34,35 (and our unpublished observations), a consistent decrease was measured in neurons. 31,35,37,38 The R192Q mutation decreased the current density at high voltages in transfected neurons but increased it in transfected HEK293 cells. 31,34,37,38 Because the same mutation did not affect the whole-cell P/Q Ca 2ϩ current density elicited by strong depolarizations in neurons of knockin mice expressing Ca V 2.1 channels at their endogenous level, the changes in transfected cells likely reflect changes in the number of functional channels in the membrane that might be an artifact of overexpression.…”
Section: Familial Hemiplegic Migraine Type 1 (Fhm1)mentioning
confidence: 99%
See 1 more Smart Citation
“…Ca 2ϩ currents supported by P/Q-type channels are more apt to facilitate during a train of brief stimuli (Inchauspe et al, 2004(Inchauspe et al, , 2007Ishikawa et al, 2005). N-type channels are more susceptible to modulation by GPCRs for neurohormones (Bourinet et al, 1996;Currie and Fox, 1997;Zhou et al, 2003;Cao and Tsien, 2005). Because Ca V 2 family members differ in responsiveness to repetitive activity and neuromodulators, controlling their contribution to presynaptic release provides a powerful way to delimit the range of regulation.…”
Section: Functional Implications Of Multiple Types Of Camentioning
confidence: 99%
“…An alternative explanation of how ␣-neurexins affect Ca 2ϩ channels could be that neurexins determine the correct spatial alignment between VDCCs and releasable vesicles, for example by anchoring VDCCs at their preferred slots within the active zone (Cao et al, 2004;Cao and Tsien, 2005). The microdomain hypothesis of Ca 2ϩ -dependent exocytosis proposes the importance of the "subsynaptic" spatial arrangement of fusioncompetent vesicles and the fusion machinery (Matthews, 1996;Klingauf and Neher, 1997;Neher, 1998).…”
Section: Effect Of ␣-Neurexins On Camentioning
confidence: 99%